A grin without a cat [videorecording (DVD)] - Marker, Chris, 1921-2012; Broadbent, Jim; Cusack, Cyril, 1910-1993; Montand, Yves, 1921-1991; Périer, François; Signoret, Simone, 1921-1985 (Icarus Films Home Video, 2009)
An overview of the worldwide political upheavals during the Sixties and Seventies. Interweaves footage from the Vietnam War and the antiwar protests in the U.S., May '68 in Paris, the Soviet invasion of Czechoslovakia, Salvador Allende and the coup in Chile, Che Guevara and Regis Debray in Bolivia, the Shah of Iran, Fidel Castro, et alia. Contains official images, film clips, news coverage trims and neglected reels.